1992
DOI: 10.1149/1.2221260
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of  CO 2 on Fluorine‐Doped SnO2 Thin‐Film Electrodes

Abstract: The reduction process of fluorine-doped SnO~ (SnQ:F) electrode in the presence of CO2 was investigated by x-ray diffraction, x-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM), colorimetry, and gas chromatography. It has been found that a SnQ:F with (200) preferred orientation undergoes the following five reduction stages:i. Oxygen-defect formation and constant hydrogen evolution.2. Acceleration of oxygen-defect formation and hydrogen evolution. At this stage, formyl -HCO-and methoxy -C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…In this way less stable oxides are avoided, improving the overall stability of the material. Nevertheless, electrodeposition at very low potentials as well as CO 2 reduction 35 will lead to dissolution of Sn from FTO. Moreover, in chloride containing electrolytes stability of FTO can be an issue 37, 38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way less stable oxides are avoided, improving the overall stability of the material. Nevertheless, electrodeposition at very low potentials as well as CO 2 reduction 35 will lead to dissolution of Sn from FTO. Moreover, in chloride containing electrolytes stability of FTO can be an issue 37, 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ITO and FTO were studied in a comprehensive overview of substrate materials for electrochemical applications, in which a broader stability of FTO was claimed 25 . Most of the results on stability originate from pre- and post-measurements of the oxides resistivity, capacitance, optical properties, and surface composition 1, 3, 15, 16, 2635 . Only in a few works dissolution was actually estimated, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The binding energy of Sb 3d and Sn 3d are consistent with Sb and Sn in predominantly 5+ and 4+ oxidation states, respectively. 32,35,36 However, while the Sb 3d XPS data show predominantly Sb in the 5+ oxidation state, the presence of a small amount of Sb 3+ would be almost indiscernible, since the binding energies of the 3d electrons on the +5 and +3 oxidation states are separated by only about 3 eV. 37,38 Fig .…”
Section: Local Electronic Environment and Oxidation State Of Cumentioning
confidence: 97%
“…44 The two peaks at 494.5 and 486.1 eV were consistent with the XPS spectrum of Sn 3d. 45,46 The above results suggested that SnR-Co-P 2 W 15 in the lm exists in its oxidized form. The binding energy located at 530.3 and 531.9 eV in Fig.…”
Section: View Article Onlinementioning
confidence: 81%